Large B-cell lymphoma with IRF4 rearrangement and follicular Pattern: A differential diagnosis of follicular lymphoma - Do Hwan Kim; Shaoying Li; Sofia Garces; Jie Xu (Elsevier, 2022)
Background: Large B-cell lymphoma with IRF4 rearrangement (LBCL-IRF4) is a rare subtype of large B-cell lymphoma characterized by strong and uniform IRF4/MUM1 expression resulting from IRF4 rearrangement, mostly with immunoglobulin heavy chain. LBCL-IRF4 was first included as a provisional entity in the revised 4th edition of WHO classification in 2017. Aim: To summarize the updated clinicopathological and cytogenetic molecular findings of LBCL-IRF4 and to help distinguish it from the other lymphomas which may cause diagnostic confusion. Methods: We reviewed: (1) the WHO Classification of Tumor of Hematopoietic and Lymphoid Tissues (4th edition, 2017); (2) the studies of LBCL-IRF4 available on PubMed including those published after the 4th edition of WHO Classification. We also described a case of LBCL-IRF4 including morphology, immunophenotype, and FISH result. Conclusion: LBCL-IRF4 can exhibit a spectrum of morphology and is characterized by strong and uniform IRF4/MUM1 expression. LBCL-IRF4 should be included in the differential diagnosis when a lymphoma has the morphology of diffuse large B-cell lymphoma and/or high-grade follicular lymphoma in the head and neck region of a young patient and coexpression of germinal center B-cell markers and strong IRF4/MUM1. LBCL-IRF4 responds well to chemotherapy and is associated with favorable prognosis.